SISTEM PENDUKUNG KEPUTUSAN UNTUK MEMPREDIKSI JUMLAH PAKAIAN DENGAN MENGGUNAKAN METODE WEIGHT MOVING AVERAGE DAN EXPONENTIAL SMOOTHING (Studi Kasus di Toko Rookieinside Yogyakarta) - Eko Prasetio; Mardiana Irawaty (Compiler, 2014)
Rookieinside is a store that moves in the field convection. Rookieinside had a bad in the determination of goods production which must be manufactured for sale and sometimes experience of excess supply in stock goods in the warehouse. Rookieinside requires a tool aids that can help and to maximize their performance in forecasts of work that must be manufactured so that work was not pile up in the warehouse. This application is made by using this method Weight Moving Average and Smoothing Exponential. Result of this application information about the number of record amounts that might have happened in the same will come. This application is useful to take a decision in determines the amount of work that will be produced in next period.